Perception of future teachers professional competences level at Faculty of Science, Palacký University Olomouc - Jana Slezáková (Paidagogos - Society For Philosophy, Theory and Praxis of Education, 2022)
The paper aims to identify and propose possible solutions in the case of perception of the level of professional competencies of first-year students of the follow-up study of teaching at the Faculty of Science, Palacký University Olomouc, from the perspective of their head teachers. Branch, diagnostic, information, managerial and communication competencies were selected. The theoretical part presents the characteristics of competencies from the perspective of selected authors, followed by an overview and characteristics of teacher competencies and a description of teacher competencies as means for successful development of professional skills. Furthermore, the organization of the first continuous pedagogical training at the Faculty of Science, Palacký University Olomouc is described. As part of the exploratory survey, a semi-structured questionnaire was created, which was attended by a total of 60 secondary and primary school teachers in the Olomouc Region. Its aim was determined by the way in which teachers evaluate the competencies of teacher students for their first continuous pedagogical training. The discussion shows the summary of the results of the questionnaire survey by the leading teachers of training. In the end the analysis of the importance of the implementation of pedagogical training at the Faculty of Science, Palacký University Olomouc is supplemented by subjects aimed at improving the current situation.